Duodenoduodenal intussusception: two case reports with different lead points - Brahmbhatt, Rutu A.; Patel, Drupad G.; Chaudhary, Pranav B. (International Surgery Journal, 2024)
Intussusception occurs when one portion of the bowel invaginates into an immediately adjacent segment, almost invariably it is the proximal into the distal. Duodenoduodenal intussusception is a rare condition that is in general caused by a tumour either benign or malignant. However duodenal intussusception is an extremely rare entity as duodenum is a fixed retroperitoneal structure. The lead point of intussusception is usually a Meckels’s diverticulum, a Peutz-Jeghers polyp or intestinal adenomas. We describe two case reports of duodenoduodenal intussusception secondary to a tubulovillous adenoma and juvenile hamartomatous polyp ((Peutz Jegher’s polyposis) that caused intussusception in a 17-year-old female and 11-year-old male respectively. Both cases had underlying abnormalities acting as lead points with different etiologies. We resected the tumour mass from both patients successfully. This report describes the rare case of isolated adenoma of the 3rd part of the duodenum and Peutz Jegher polyp in the jejunum presented as duodenoduodenal and duodenojejunal type of enteroenteric intussusception fully treated by segmental resection of the duodenum and jejunum and doing well on follow up.